2013
DOI: 10.1093/nar/gkt223
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein S7 regulates arsenite-induced GADD45  expression by attenuating MDM2-mediated GADD45  ubiquitination and degradation

Abstract: The stress-responding protein, GADD45α, plays important roles in cell cycle checkpoint, DNA repair and apoptosis. In our recent study, we demonstrate that GADD45α undergoes a dynamic ubiquitination and degradation in vivo, which process can be blocked by the cytotoxic reagent, arsenite, resulting in GADD45α accumulation to activate JNKs cell death pathway, thereby revealing a novel mechanism for the cellular GADD45α functional regulation. But the factors involved in GADD45α stability modulations are unidentifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
0
29
2
Order By: Relevance
“…Recently, it has been reported that MDM2 functions as an E3 ubiquitin ligase for GADD45A. Enhanced association between MDM2 and RPS7 following arsenite treatment attenuated MDM2-mediated GADD45A ubiquitination, resulting in GADD45A protein stabilization and apoptosis (41). Interestingly, our microarray analysis identified RPS27L, a direct TP53 target, that modulates cell fate in response to genotoxic stress (42), to be upregulated only in those sarcomas in which robust apoptotic responses were observed.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, it has been reported that MDM2 functions as an E3 ubiquitin ligase for GADD45A. Enhanced association between MDM2 and RPS7 following arsenite treatment attenuated MDM2-mediated GADD45A ubiquitination, resulting in GADD45A protein stabilization and apoptosis (41). Interestingly, our microarray analysis identified RPS27L, a direct TP53 target, that modulates cell fate in response to genotoxic stress (42), to be upregulated only in those sarcomas in which robust apoptotic responses were observed.…”
Section: Discussionmentioning
confidence: 71%
“…S7 forms a complex with GADD45α (growth arrest and DNA damage inducible gene 45α), which regulates DNA repair, cell cycle checkpoints, and apoptosis. S7 interacts with both MDM2 and GADD45α, protecting GADD45α from MDM2‐mediated ubiquitination and degradation . However, S7 mutants lacking the ability to bind MDM2 do not stabilize GADD45α, indicating the importance of the RP–MDM2 interplay (Fig.…”
Section: Ribosomal Proteins and Nucleolar Stressmentioning
confidence: 95%
“…However, S7 mutants lacking the ability to bind MDM2 do not stabilize GADD45α, indicating the importance of the RP–MDM2 interplay (Fig. H) …”
Section: Ribosomal Proteins and Nucleolar Stressmentioning
confidence: 99%
“…Activated p53 then transactivates its downstream targets to induce growth arrest and apoptosis to block tumorigenesis. (Adilakshmi and Laine, 2002;Bai et al, 2014;Barlow et al, 2010a;He and Sun, 2007;Jang et al, 2012a;Jeon et al, 2008;Khanna et al, 2003;Li et al, 2010;Naora et al, 1998;Neumann and Krawinkel, 1997;Russo et al, 2013;Takagi et al, 2005;Wu et al, 2012;Yang et al, 2012;Zhu et al, 2009) Cell cycle S3, S5, S6, S7, S14, S15, S19, S20, S25, S26, S27, S27L, S27a, L3, L5, L6, L7, L11, L13, L23, L26, L31, L34, L37, L41 (Cui et al, 2014;Daftuar et al, 2013;Dai et al, , 2007bGao et al, 2013;Gou et al, 2010;Iadevaia et al, 2010;Kobayashi et al, 2006;Maruyama et al, 2014;Matragkou et al, 2008;Moorthamer and Chaudhuri, 1999;Neumann and Krawinkel, 1997;Russo et al, 2013;Sun et al, 2011;Takagi et al, 2005;Wang et al, 2011a;Wanzel et al, 2008;Xiong et al, 2011;Zhang et al, 2013Zhang et al, , 2015Zhou et al, 2013a) Cell proliferation S6, S9, S13, S14, S15a, S24, S27, L6, L8, L11, L15, L17, L26, L29, L31, L34, L36a (Dai et al, 2007a;Gou et al, 2010Kim et al, 2004;Li et al, 2010…”
Section: Apoptosismentioning
confidence: 99%